Hermeneutics: the German Contribution to Legal Interpretation (2014)
Ths essay seeks to recognize the contributions made by the German philosophers FriedrichSchleiermacher, Wilhelm Dilthey and Hans Georg Gadamer, in the fild of hermeneutics,which ceased to be exclusively a subject of theology, extending its practical uses, preciselybecause of these contributions, to the legal world, mainly in legal interpretation as the workof judges.